Information literacy and social innovation: interdisciplinarity in focus - Santos, Alessandra de Souza; Maia, Luiz Cláudio Gomes; Pinheiro, Marta Macedo Kerr (InCID: Revista de Ciência da Informação e Documentação, 2022)
This article aims at analyzing the concepts of social innovation and information literacy, considering the interdisciplinary character of both disciplines, in order to highlight similarities that exist in the two themes. Social innovation aims at social transformation by means of generating changes in social practices, what implies interdisciplinarity since it addresses the ways in which society is transformed in the most diverse areas. Information literacy is a meta-competence capable of helping the individual to deal with information needs, which are specific to each context in an informationally asymmetric society. Information literacy is at the heart of lifelong learning and it is essential for full human development in all its dimensions. Thus, information literacy must be developed across all disciplines and contexts. One concludes that there is interdisciplinarity not only in the field of social innovation but also in the field information literacy, so that one can suggest future studies that focus on the correlation between the two disciplines in the light of interdisciplinarity, since both are intended to solve contemporary social problems